Short-term mission an ethnography of Christian travel narrative and experience - Howell, Brian M. (Downers Grove, IL : IVP Academic, 2012)
Drawing on the anthropology of tourism and pilgrimage, he shows how short-term mission (STM) combines these elements with Christian purposes of mission to create its own distinct narrative. He provides a careful historical survey of the development of STM and then offers an in-depth ethnographic study of a particular mission trip to the Dominican Republic. He explores how participants remember and interpret their experiences, and he unpacks the implications for how North American churches understand mission, grapple with poverty and relate to the larger global church. --from publisher description
"It changed my life": short-term mission and Christian narratives of travel -- "Are you for them or against them?": defining short-term mission -- That's no missionary!": redefining mission and the missionary establishment -- "Youth try the impossible!": youth movements and short-term mission -- "It will change your life": short-term mission and Central Wheaton Church -- "Remember, these are real missions": embodying a missionary narrative at Central Wheaton Church -- "Pour out your soul": living the narrative of short-term mission -- "Of course you always grow close to God on a mission trip": (re)narrating short-term mission -- "Just bring greetings": creating a new narrative for short-term mission -- "And what does the Lord require of you?": suggestions and an encouraging postscript.
Includes bibliographical references (p. [237]-254) and indexes.
Description based on print version record.
Keywords: Short-term missions; Short-term missions; RELIGION / Christian Ministry / Missions; Electronic books